2015
DOI: 10.1016/j.proci.2014.06.139
|View full text |Cite
|
Sign up to set email alerts
|

PAH formation and soot morphology in flames of C4 fuels

Abstract: In this work, we describe experimental studies on the formation of polycyclic aromatic hydrocarbons (PAH's) in opposed-flow atmospheric-pressure flames of n-butane, i-butane, i-butene, and i-butanol and on the morphology of nascent soot particles sampled from premixed atmospheric-pressure flames of the same fuels. To identify the major contributors to the molecular growth mechanism in opposed-flow flames, we employed flame-sampling molecular-beam mass spectrometry with electron ionization (EI) and in situ gas-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 39 publications
4
30
0
Order By: Relevance
“…The flame conditions were identical to the ones reported in Ref. [49] and are provided here only as Supplementary Material. The fuels were chosen because their respective combustion chemistry are interesting research topics as outlined in Refs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The flame conditions were identical to the ones reported in Ref. [49] and are provided here only as Supplementary Material. The fuels were chosen because their respective combustion chemistry are interesting research topics as outlined in Refs.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental approach used to record the flame-sampled mass spectra has been detailed in Ref. [49]. In short, opposed-flow fuel-Ar/O 2 -Ar diffusion flames were established at atmospheric pressure between the two outlets of a home-built burner system [54] while regulating the respective gas flows with an absolute precision of ±0.5 % using calibrated mass flow controllers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 (b). From the past studies [20,25,82] , it has been shown that in the formation of benzene ring the propargyl radical plays an important role. Therefore, the ranking of A 1 -ring formation (benzene, C 6 H 6 ) in Fig.…”
Section: Non-premixed Counterflow Flame Simulationsmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24]. Recently, Schenk et al [25] have proposed the methyland phenyl-addition pathways of the PAH formation. In addition, the odd-carbon-atom pathways have been introduced as possible reaction routes of the incipient PAH formation, as the propargyl http://dx.doi.org/10.1016/j.combustflame.2016.05.009 0010-2180/© 2016 The Combustion Institute.…”
Section: Introductionmentioning
confidence: 99%